2020
DOI: 10.21608/epsj.2020.96408
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interaction Between Number of Day Light Hours and Dietery Protein Levels on Productive, Physiological and Immunological Performance of Two Developed Strain Chickens.

Abstract: This experiment was carried out on the Matrouh and Silver Montazah strains which used 120 females + 12 males for each strain to study the effect of interaction between number of day light hours and dietary protein levels on productive, physiological and immunological performance. The groups were as follows: The first group was taken 17 hours lighting /day + 16% dietary protein (control group); the second group was taken 17 hours lighting /day + 18% dietary protein; the third group was taken 15 hours lighting /… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…The data of this experiment indicate an increase in the number of RBC, the level of PCV ,hemoglobin ,white cells and lymphocytes at the intensity of illumination of 25 and 45 lux compared with the control group and 0.6 lux and this corresponds to what was indicated by Okyere et al (16) until the exposure of laying hens to 16 hours of illumination per day, which led to an elevate in the number of red cells, white cell and the level of PCV, as Mohamed et al (15) indicated that exposure of broilers for 45 days to a monochromatic light of 20 lux led to an increase in the numbers of red blood cells, Hb and PCV. These results are consistent with those indicated by Hassan (10) if illumination for 17 hours in poultry led to an increase in lymphocytes, heterophiles, white cell, red cell, PCV and stress index. This increase can be participated to the improvement in the ecosystem and the oxidative state of the bird, as it was proven that the photoperiod affects the microorganisms present in the bird's intestines (12) and that the gut microbiota affects the functions of the organs and the immune system of birds (27).…”
Section: Statistical Analysis a One-way Analysis Of Variance Has Been...supporting
confidence: 93%
“…The data of this experiment indicate an increase in the number of RBC, the level of PCV ,hemoglobin ,white cells and lymphocytes at the intensity of illumination of 25 and 45 lux compared with the control group and 0.6 lux and this corresponds to what was indicated by Okyere et al (16) until the exposure of laying hens to 16 hours of illumination per day, which led to an elevate in the number of red cells, white cell and the level of PCV, as Mohamed et al (15) indicated that exposure of broilers for 45 days to a monochromatic light of 20 lux led to an increase in the numbers of red blood cells, Hb and PCV. These results are consistent with those indicated by Hassan (10) if illumination for 17 hours in poultry led to an increase in lymphocytes, heterophiles, white cell, red cell, PCV and stress index. This increase can be participated to the improvement in the ecosystem and the oxidative state of the bird, as it was proven that the photoperiod affects the microorganisms present in the bird's intestines (12) and that the gut microbiota affects the functions of the organs and the immune system of birds (27).…”
Section: Statistical Analysis a One-way Analysis Of Variance Has Been...supporting
confidence: 93%